CRISPR Gene Editing of Human Primary NK and T Cells for Cancer Immunotherapy - Elmas, Ezgi; Saljoughian, Noushin; de Souza Fernandes Pereira, Marcelo; Tullius, Brian P.; Sorathia, Kinnari; Nakkula, Robin J.; Lee, Dean A.; Naeimi Kararoudi, Meisam (Frontiers in Oncology, 2022)
Antitumor activity of immune cells such as T cells and NK cells has made them auspicious therapeutic regimens for adaptive cancer immunotherapy. Enhancing their cytotoxic effects against malignancies and overcoming their suppression in tumor microenvironment (TME) may improve their efficacy to treat cancers. Clustered, regularly interspaced short palindromic repeats (CRISPR) genome editing has become one of the most popular tools to enhance immune cell antitumor activity. In this review we highlight applications and practicability of CRISPR/Cas9 gene editing and engineering strategies for cancer immunotherapy. In addition, we have reviewed several approaches to study CRISPR off-target effects.